RELIGIOUS BOOKS OF LITHUANIAN JEWS IN 1928–1940 “BIBLIOGRAFIJOS ŽINIOS” - JUONYTĖ, ŽIVILĖ (Knygotyra, 2014)
The object of this article is Lithuanian Jews' religious books, printed in Hebrew or Yiddish in the Lithuanian territory in 1928-1940 and included in issues of the magazine “Bibliografijos žinios”, published by the Lithuanian Bibliographical Institute. The article analyzes the polygraphic base, repertoire and features of Jewish religious books through their reflection in “Bibliografijos žinios”. In addition, the article also aims at evaluating "Bibliografijos žinios" as a source of bibliographical information and its possible usage in future research.“Bibliografijos žinios” was the only interwar publication that aimed to systematically record Lithuania's multilingual printing productions. 136 Jewish religious books were reflected in the interwar period in “Bibliografijos žinios”. Analysis of their bibliographical information revealed that Movšovičiaus and Kagano printing house in Kėdainiai had produced most of the Jewish religious books, while the temporary capital Kaunas with Joselevičiaus and other printing houses remained in second place. On average, 10–11 religious books were published yearly. Most religious books were printed in Hebrew, and several in Yiddish. Lithuanian language was occasionally used to present minimal information about the book in its title or cover pages. Explanations and comments of Talmud amounted to almost half of all publications. Another rich group of interwar Jewish religious books was lessons and preaching of rabbis. Many of these books were original works, written by local religious authorities.Several disadvantages, related to Jewish books' reflection in “Bibliografijos žinios”, including, but not limited to inaccurate transcription and incomplete data, were found during the analysis. Consequently, further research of the Jewish books in Lithuania is advised to use additional information sources along “Bibliografijos žinios”.
Keywords: ...